Business and administrative communication - Locker, Kitty O.; Kienzler, Donna S. (Boston McGraw-Hill, 2008)
Covering the scope of topics in oral and written business communication, this book conveys advice to students through its research base.
Part one : the building blocks of effective messages -- 1. Business communication, management, and success ? 2. Adapting your message to your audience -- 3. Building goodwill -- 4. Making your writing easy to read -- 5. Planning, composing, and revising -- 6. Designing documents, data displays, and visuals -- Part two : job hunting -- 7. Resumes -- 8. Job application letters -- 9. Job interviews, follow-up messages, job offers, and first jobs -- Part three: basic business messages -- 10. Informative and positive messages -- 11. Negative messages -- 12. Persuasive and sales messages -- Part four: Interpersonal communication -- 13. Communicating across cultures -- 14. Working and writing in groups -- Part five : reports -- 15. Planning, proposing, and researching reports -- 16. Analyzing information and writing reports -- 17. Making oral presentations -- Appendices A. formats for letters, memos, and e-mail messages -- B. Writing correctly -- C. Video cases to accompany manager's hot seat.
Keywords: Business communication; Communication in management